Loanwords in the context of the modern language situation (Eurasian Journal of Philology Science and Education, 2018)
The article investigates borrowing as a multidimensional phenomenon that has a stylistic, psycholinguistic, pragmatic and aesthetic nature, and requires serious study and linguodidactics work. Borrowing is characterized as a dominant process in the modern language space, the formation of which wasinfluenced by radical social and political changes of recent years. In this article the author analyzes thelinguistic and extra-linguistic reasons the process of cutting and even aggressive revitalization use of foreign words, which leads to serious problems in speech practice, describes the ways and means of assimilation of loanwords in the modern Russian language.Among the linguistic reasons they are named suchreasons as the absence in the lexical system of Russian language of names for new concepts; the need tolay out the features of the subject or actualize the expressive shades of the word; using the potential ofborrowed words of a certain word-formation model, etc. On the basisofthe analysis of various linguisticfacts, it is affirmed that a new communicative space has emerged that changes stereotypes about literaryand non-literary, old and new, its own and others’ language.